Botrytis cinerea tolerates phytoalexins produced by Solanaceae and Fabaceae plants through an efflux transporter BcatrB and metabolizing enzymes - Bulasag, Abriel Salaria; Camagna, Maurizio; Kuroyanagi, Teruhiko; Ashida, Akira; Ito, Kento; Tanaka, Aiko; Sato, Ikuo; Chiba, Sotaro; Ojika, Makoto; Takemoto, Daigo (Frontiers in Plant Science, 2023)
Botrytis cinerea, a plant pathogenic fungus with a wide host range, has reduced sensitivity to fungicides as well as phytoalexins, threatening cultivation of economically important fruits and vegetable crops worldwide. B. cinerea tolerates a wide array of phytoalexins, through efflux and/or enzymatic detoxification. Previously, we provided evidence that a distinctive set of genes were induced in B. cinerea when treated with different phytoalexins such as rishitin (produced by tomato and potato), capsidiol (tobacco and bell pepper) and resveratrol (grape and blueberry). In this study, we focused on the functional analyses of B. cinerea genes implicated in rishitin tolerance. LC/MS profiling revealed that B. cinerea can metabolize/detoxify rishitin into at least 4 oxidized forms. Heterologous expression of Bcin08g04910 and Bcin16g01490, two B. cinerea oxidoreductases upregulated by rishitin, in a plant symbiotic fungus Epichloë festucae revealed that these rishitin-induced enzymes are involved in the oxidation of rishitin. Expression of BcatrB, encoding an exporter of structurally unrelated phytoalexins and fungicides, was significantly upregulated by rishitin but not by capsidiol and was thus expected to be involved in the rishitin tolerance. Conidia of BcatrB KO (DbcatrB) showed enhanced sensitivity to rishitin, but not to capsidiol, despite their structural similarity. DbcatrB showed reduced virulence on tomato, but maintained full virulence on bell pepper, indicating that B. cinerea activates BcatrB by recognizing appropriate phytoalexins to utilize it in tolerance. Surveying 26 plant species across 13 families revealed that the BcatrB promoter is mainly activated during the infection of B. cinerea in plants belonging to the Solanaceae, Fabaceae and Brassicaceae. The BcatrB promoter was also activated by in vitro treatments of phytoalexins produced by members of these plant families, namely rishitin (Solanaceae), medicarpin and glyceollin (Fabaceae), as well as camalexin and brassinin (Brassicaceae). Consistently, DbcatrB showed reduced virulence on red clover, which produces medicarpin. These results suggest that B. cinerea distinguishes phytoalexins and induces differential expression of appropriate genes during the infection. Likewise, BcatrB plays a critical role in the strategy employed by B. cinerea to bypass the plant innate immune responses in a wide variety of important crops belonging to the Solanaceae, Brassicaceae and Fabaceae.